Utilization of Fermented Conch Mas (Pomacea cannaliculata) Flour with Eco Enzymes on Egg Production and Quail Egg Weight - N. Ginting; N. Ketaren; situmeang, feri junedi (Talenta Publisher, 2022)
Feed is one of the determining factors for the success of livestock production because it takes up 70-80% of production costs. High-protein feed ingredients are one of the high-priced feed ingredients, so it is necessary to use non- conventional feeds. The golden snail is a pest that interferes with rice growth in agricultural areas. The golden snail has a high protein content so it is very efficient to be used as a protein source feed ingredient. In this study, fermented golden snails in the form of flour were used as a substitute for fish meal in the rations of laying quail. The design used was a completely randomized design (CRD) using 4 treatments and 5 replications, namely P0 = 8% fish flour, P1 = 4% fermented golden snail flour, P2 = 8% fermented golden snail flour, P3 = 12% fermented golden snail flour . The research parameters were feed consumption, egg production, egg weight, feed conversion. The results showed that the utilization of fermented golden snail flour up to 12% had a very significant effect (P<0.01) on feed consumption, egg production and feed conversion with an average of 108.573g/e/week, 33.476%, and 1 ,77. However, it gave an insignificant impact on egg weight with an average value of 10.15 g/grain. The highest ration consumption was at P0 of 114,488g/e/week, the highest egg production was at P3 of 40.667% and the best feed conversion was at P3 of 1.06. The results showed that the use of fermented golden snail flour using 12% Eko enzymes was suitable to be used as a substitute for fish meal